2013
DOI: 10.1021/jp4003559
|View full text |Cite
|
Sign up to set email alerts
|

Parallel β-Sheet Fibril and Antiparallel β-Sheet Oligomer: New Insights into Amyloid Formation of Hen Egg White Lysozyme under Heat and Acidic Condition from FTIR Spectroscopy

Abstract: Hen egg white lysozyme (HEWL) is widely used as a model protein for amyloid research. In this study, we aim to use Fourier transform infrared (FTIR) spectroscopy to gain new structural insights into amyloid formation of HEWL under heat and acidic condition. We reveal that the fibril-forming solution of HEWL has the capability to form fibril and oligomer with distinct β-sheet configurations under different temperatures. Amyloid fibril with parallel β-sheet configuration is formed at elevated temperature, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
137
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(166 citation statements)
references
References 67 publications
(138 reference statements)
27
137
1
Order By: Relevance
“…This is as expected. 33 On the other hand, an on-pathway oligomeric intermediate could also form at the same temperature according to our prediction. This means that we would have two different aggregates coexisting in the incubation solution.…”
Section: ■ Results and Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This is as expected. 33 On the other hand, an on-pathway oligomeric intermediate could also form at the same temperature according to our prediction. This means that we would have two different aggregates coexisting in the incubation solution.…”
Section: ■ Results and Discussionsupporting
confidence: 81%
“…Details of the making of the IR cell have been described previously. 33 The absorption spectrum of solvent D 2 O (pD = 2) can be taken in the same manner. Solvent subtraction from each original protein absorption spectrum is not necessary as we directly perform spectral subtraction between two original spectra to obtain difference spectrum in this study.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…An experiment of hen egg white lysozyme has revealed that non-b-sheet oligomers exist as off-pathway aggregates. [37] Figure 9 indicates that the structural contributors for the shoulder (k55:5 Å ) of P strð19Þ cano ðk; v; TÞ in Figure 8 are the antiparallel b-sheets, parallel b-sheets, and the cross-structures. Note that P strð19Þ cano ðk; v; TÞ is the equilibrated distribution for the two-chain system.…”
Section: Two-dimensional Free-energy Landscapementioning
confidence: 99%
“…Later, the research team of Eisenberg revealed the structure of an off-pathway, cylindrical oligomer of a segment of the amyloid-forming protein αB crystallin, that resembled a β-barrel composed of six antiparallel β-strands (72). We and other groups demonstrated that amyloidogenic proteins, such as Aβ, pass through an antiparallel β-sheet structured state, corresponding to oligomers, before undergoing a transition in structure to parallel β-sheet fibrils (58)(59)(60)(73)(74)(75). Recently, the group of Tycko demonstrated that Aβ , containing the FAD-linked Iowa D23N mutation and causing CAA, assembled into antiparallel β-sheet structured fibrils that were thermodynamically metastable and had a ribbon-like appearance (39).…”
Section: Discussionmentioning
confidence: 97%
“…Therapy consists mainly of treating cognitive decline and behavioural symptoms. Five cholinesterase inhibitors and one N-methyl-D-aspartate (NMDA) receptor antagonist (memantine) have been approved by the US Food and Drug Administration (FDA) for treatment of cognitive decline (75). Acetylcholinesterase inhibitors are thought to improve functioning of the cholinergic system in AD patients by binding to acetylcholinesterase in the synaptic cleft, preventing it to break down acetylcholine, a neurotransmitter involved in learning and memory (76).…”
Section: Current Ad Drugs Temporarily Reduce Disease Symptomsmentioning
confidence: 99%